1976
DOI: 10.1070/qe1976v006n01abeh010825
|View full text |Cite
|
Sign up to set email alerts
|

Resonant buildup of surface oscillations of a liquid drop by an electromagnetic field

Abstract: We report on a preliminary investigation on the maskless implantation of Ge ions into Si for the production of Si 1−x Ge x microstructures. The technique employs a focused ion beam system using a liquid metal alloy ion source. Closely spaced simple structures down to about 1 µm in width, with well-defined boundaries, have been produced. On some of these structures, spreading resistance measurements were carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The ponderomotive force (4) will excite harmonic acoustic vibrations in the nanoparticle. Resonant buildup of surface oscillations of a liquid drop of submicron size by an electromagnetic field was theoretically considered in [23]. It was shown that the effective impact on a liquid submicron particle can be realized by biharmonic laser radiation if the difference frequency proves to be equal to the particle's acoustic eigenfrequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ponderomotive force (4) will excite harmonic acoustic vibrations in the nanoparticle. Resonant buildup of surface oscillations of a liquid drop of submicron size by an electromagnetic field was theoretically considered in [23]. It was shown that the effective impact on a liquid submicron particle can be realized by biharmonic laser radiation if the difference frequency proves to be equal to the particle's acoustic eigenfrequency.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the effective impact on a liquid submicron particle can be realized by biharmonic laser radiation if the difference frequency proves to be equal to the particle's acoustic eigenfrequency. The amplitude of oscillation is determined by the following expression [23]:…”
Section: Discussionmentioning
confidence: 99%
“…The light scattered by the droplet to low angles relative to the direction of the laser's beam, going through the optical elements (5-7), falls into the photomultiplyer (8), connected to the spectrum ana'yzer (9). The system of the optical elements (5)(6)(7) is designed to stop the background light, occurring due to laser scattering from different optical elements of the scheme. The light scattered by a droplet is converted by the mirror (5) into a parallel beam and freely passes the transparent glass (7), w'hile the parasitic scattered light is kept by the nontransparent shielding drawn in the center of the glass (7).…”
Section: Experimental Registration Of Ils From Dso Effectmentioning
confidence: 99%